InN Quantum Dots by Metalorganic Chemical Vapor Deposition for Optoelectronic Applications - Reilly, Caroline E.; Keller, Stacia; Nakamura, Shuji; DenBaars, Steven P. (Frontiers in Materials, 2021)
This review will cover recent work on InN quantum dots (QDs), specifically focusing on advances in metalorganic chemical vapor deposition (MOCVD) of metal-polar InN QDs for applications in optoelectronic devices. The ability to use InN in optoelectronic devices would expand the nitrides system from current visible and ultraviolet devices into the near infrared. Although there was a significant surge in InN research after the discovery that its bandgap provided potential infrared communication band emission, those studies failed to produce an electroluminescent InN device in part due to difficulties in achieving p-type InN films. Devices utilizing InN QDs, on the other hand, were hampered by the inability to cap the InN without causing intermixing with the capping material. The recent work on InN QDs has proven that it is possible to use capping methods to bury the QDs without significantly affecting their composition or photoluminescence. Herein, we will discuss the current state of metal-polar InN QD growth by MOCVD, focusing on density and size control, composition, relaxation, capping, and photoluminescence. The outstanding challenges which remain to be solved in order to achieve InN infrared devices will be discussed.